Career guidance and the policy in preparing of The future of the child development (Research at Sukamiskin Institute Of Special Coaching In Bandung West Java Indonesia) - Engkus, Siti Chodijah dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this study are: First, to know the types of guidanceprants inInstitutions Special Coaching Children Bandung. Second, to know thetechniques of career guidance at the Institute of Special Education ChildrenBandung. Third, to find out the results of career guidance at the Institute ofChild Development Special Bandung. This research uses descriptive methodwith qualitative approach, by collecting data and information throughinterview method, observation, documentation, which then analyzed bywriter by way of describing all information received from informant withthe required data. Then the authors conclude the information to answer thepurpose of research. The career guidance at the Bandung ChildDevelopment Institution is in line with the career guidance goals set forth bySalahudin that the goals of career guidance are self-understanding,knowledge of the world of work, positive attitude toward the world of work,and the ability to plan for the future. The results show that career guidanceheld at LPKA helps students to plan and prepare for their future accordingto the goals of such career guidance through various types and techniques ofcareer guidance.Keywords: Career guidance, Planning, Future